2016
DOI: 10.1159/000446499
|View full text |Cite
|
Sign up to set email alerts
|

<b><i>TRPV1</i></b> Gene Polymorphisms Are Associated with Type 2 Diabetes by Their Interaction with Fat Consumption in the Korean Genome Epidemiology Study

Abstract: Background: Different transient receptor potential vanilloid 1 (TRPV1) variants may be differently activated by noxious stimuli. Aim: We investigated how TRPV1 variants modulated the prevalence of type 2 diabetes and specific gene-nutrient interactions. Methods: Among 8,842 adults aged 40-69 years in the Korean Genome Epidemiology Study, the associations between TRPV1 genotypes and the prevalence of type 2 diabetes as well as their gene-nutrient interactions were investigated after adjusting for the covariates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 40 publications
(71 reference statements)
0
38
0
Order By: Relevance
“…The area under the curve (AUC) of glucose and insulin was calculated by the trapezoidal rule. Insulin resistance was assessed using the homeostasis model assessment estimate (HOMA) of insulin resistance (HOMA-IR = fasting insulin levels [µIU/mL] × fasting glucose levels [mM]/22.5) [22]. Insulin secretion capacity was represented by HOMA-B.…”
Section: Glucose Metabolism and Other Biochemical Parameters Of The Kmentioning
confidence: 99%
See 3 more Smart Citations
“…The area under the curve (AUC) of glucose and insulin was calculated by the trapezoidal rule. Insulin resistance was assessed using the homeostasis model assessment estimate (HOMA) of insulin resistance (HOMA-IR = fasting insulin levels [µIU/mL] × fasting glucose levels [mM]/22.5) [22]. Insulin secretion capacity was represented by HOMA-B.…”
Section: Glucose Metabolism and Other Biochemical Parameters Of The Kmentioning
confidence: 99%
“…Insulin secretion capacity was represented by HOMA-B. HOMA-B was calculated as (20 × fasting insulin levels)/(fasting glucose levels -3.5) [22]. The subjects were categorized into 2 groups by the HOMA-IR with the cut-off level of 2.0 (the 75th percentile) and the HOMA-B with the cut-off point of 120 (the 25th percentile).…”
Section: Glucose Metabolism and Other Biochemical Parameters Of The Kmentioning
confidence: 99%
See 2 more Smart Citations
“…A Korean Genome Epidemiology Study demonstrated that individuals with the minor alleles of the TRPV1 single nucleotide polymorphisms (SNPs) rs161364 T>C and rs8065080 T>C were negatively associated with the prevalence of T2DM. They also determined that carriers of the minor allele of both SNPs have a lower risk of diabetes with a high-fat diet but individuals with the major alleles are at a higher risk of T2DM when consuming high-fat diets [215]. …”
Section: Diet-gene Interaction and Risk Of T2dmmentioning
confidence: 99%